Open resection and reconstruction of a Nasoseptal Chondrosarcoma: case report and literature review - Changseok Lee; David Forner; Martin Bullock; Matthew H. Rigby; Martin Corsten; Jonathan R. Trites; S. Mark Taylor (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Primary chondrosarcomas of the nasal septum are rare, with a variety of clinical features that evade detection and treatment. While endoscopic surgery has become increasingly accessible, open approaches may be needed to provide adequate visualization for tumour ablation and reconstruction. We report the resection and reconstructive considerations of a septal chondrosarcoma. Case presentation A 75-year-old woman presented with a 3-year history of a slow growing, firm mass in the nasal tip causing protrusion and septal fullness. Computed Tomography scan of the paranasal sinuses revealed a well-circumscribed, 2.2 cm mass at the anterior nasal septum extending into the right vestibule. Biopsy of the cartilaginous lesion confirmed the diagnosis of a low-grade chondrosarcoma by histopathology. The tumour was removed using a transcolumellar open rhinoplasty approach with a large septal resection. Primary reconstruction of the surgical defect was performed using an L-shaped strut from the nasal keystone area to the columella. Follow-up examinations demonstrated no evidence of recurrent disease with satisfactory functional and cosmetic outcomes at 1-year. Conclusion This report describes a case of nasal septal chondrosarcoma successfully treated with surgical excision using an open rhinoplasty approach. Only 5–10% of chondrosarcomas are located in the head and neck region and arise rarely in the nasal septum in approximately 2–4%. With this mass, an open rhinoplasty approach was required to allow optimal exposure of the margins and to facilitate reconstruction without disruption of normal sinonasal anatomy and function. Although rare, chondrosarcoma of the nasal septum should be considered in the differential diagnosis of nasal masses.